ROLE OF NASYA IN THE MANAGEMENT OF DYSFUNCTIONAL UTERINE BLEEDING - A REVIEW - Aparna S; Maya Balakrishnan; Giby Thomas (International Journal of Ayurveda and Pharma Research, 2021)
Regular menstrual cycles with adequate quantity and duration of bleeding indicate good reproductive health, with variations in these being reflected as menorohagia, oligomenorrbea, dysmenorrbea, PCOD, infertility etc. Dysfunctional uterine bleeding is particularly common during adolescence and perimenopausal periods. It has been defined as a state of excessive uterine bleeding without clinically detectable organic, systemic and iatrogenic causes. DUB is caused by the abnormal functioning of hypothalamo – pituitary – ovarian axis. Nasya is a term applied generally when the medicine is administered through the nasal passage. It is considered as the most specific Panchakarama therapy used for the diseases of Siras (head) or Urdva jatru region, as nasal passage is regarded as the gateway to the head. In the present article the possible role of Nasya in the management of dysfunctional uterine bleeding is discussed. Nasya indirectly work on the entire body by improving the functioning of central nervous system and endocrine glands. The neurons which stimulate production of GnRH, originates from the olfactory area and GnRH is the regulator of gonadotropin hormones. The hormones of menstruation are under the control of these secreted by the pituitary. Nasya which is considered as having direct action on neuro-endocrinological system may regulate HPO axis and normalize the menstruation.